Algumas notas sobre o catecismo peninsular no século XVI : de Constantino a Frei Pedro de Santa Maria - Tavares, Pedro Vilas Boas (2014)
In this comparative study based on an internai analysis of Constantino Ponce de la Fuente's and Fr. Pedro de Santa Maria's catechistic writings, the important common attitude ascribed to the influence of Erasmian thought is emphasized, as indeed is the Portuguese author's specificity of language and sensibility. The survival of traditional forms of piety, as seen in Fr. Pedro de Santa Maria's Ordem e regimento de vida cristã (1556), corresponds eclectically to the modern forms - from Franciscan and Ignacian influences -; this concordance can, at that moment, be seen as an eloquent testimony to the «orthodox» integration of Rotterdamian mastership.